Neuroprotective potential of some terebinth coffee brands and the unprocessed fruits of Pistacia terebinthus L. and their fatty and essential oil analyses - Orhan, Ilkay Erdogan; Senol, F. Sezer; Gulpinar, A. Rifat; Sekeroglu, Nazim; Kartal, Murat; Sener, Bilge (Elsevier Sci Ltd, 2012)
In the current study, neuroprotective effects of the ethyl acetate and methanol extracts of four terebinth coffee brands and the fruits of Pistacia terebinthus L were investigated through enzyme inhibition tests against acetylcholinesterase, butyrylcholinesterase, and tyrosinase as well as antioxidant test systems. Antioxidant activity was measured using radical scavenging activity tests and metal-related tests including metal-chelation capacity, ferric-reducing antioxidant power (FRAP), and phosphomolybdenum reducing power (PRAP). The fatty oils of the coffee brands and the fruits and the fruit essential oil were examined by GC-MS. Total phenol and flavonoid contents were calculated spectrophotometrically. The extracts had moderate inhibition against butyrylcholinesterase (9.78-45.74% at 200 mu g mL(-1)) and potent scavenging activity against DPPH. They exerted strong activity in FRAP and metal-chelation tests and modest activity in PRAP test. Oleic acid was identified as the major fatty acid in the fatty oils, while alpha-pinene (26.31%) was dominant in the essential oil. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Pistacia terebinthus; Terebinth coffee; Neuroprotection; Antioxidant activity; Fatty oil; Essential oil